2017
DOI: 10.18805/lr.v0i0.8410
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic evaluation of cowpea cultivars developed for the West African Savannas

Abstract: The goal of this research was to evaluate diverse cowpea genotypes developed over the past 4 decades in the Nigerian Sudan Savannas for their agronomic performance and to identify groups of cultivars with similar quantitative characters. Characterization would facilitate the efficient synthesis of breeding populations for further improvement of cowpea. Also superior genotypes with desirable characteristics could be identified and disseminated in the dry savannas of West Africa. Significant variations were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…The current study has shown that seed yield is strongly positively correlated with number of pods, suggesting that when selection is applied for one of these traits, an indirect improvement could be observed in seed yield. The current study confirmed the previous reports for cowpea in South Africa (Gerrano et al., 2015; Gerrano, Jansen van Rensburg, & Kutu, 2019; Nkoana et al., 2019) and Nigeria (Kamara et al., 2017). Previous studies (Nkoana et al., 2019; Walle, Mekbib, Amsalu, & Gedil, 2019) showed that number of seeds per pod, number of pods per plant, and pod length had the strongest influence on seed yield.…”
Section: Discussionsupporting
confidence: 92%
“…The current study has shown that seed yield is strongly positively correlated with number of pods, suggesting that when selection is applied for one of these traits, an indirect improvement could be observed in seed yield. The current study confirmed the previous reports for cowpea in South Africa (Gerrano et al., 2015; Gerrano, Jansen van Rensburg, & Kutu, 2019; Nkoana et al., 2019) and Nigeria (Kamara et al., 2017). Previous studies (Nkoana et al., 2019; Walle, Mekbib, Amsalu, & Gedil, 2019) showed that number of seeds per pod, number of pods per plant, and pod length had the strongest influence on seed yield.…”
Section: Discussionsupporting
confidence: 92%
“…Cowpea (Vigna unguiculata L.) is grown in arid and semi-arid regions of the world where it is considered as the most drought-tolerant food legumes. The economic importance of cowpea are high protein content of the seeds (20% to 40%), N fixed biologically ranged from 73 to 354 kg N/ha per year, and the consumption of its foliage and fresh and dry grain (Kamara et al, 2017). It has been observed that there was a significant difference among cowpea genotypes with regard water deficit tolerance at the vegetative, flowering and pods filling stages (Ahmed and Suliman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We also found a positive correlation between the width of the canopy and iWUE canopy (Pearson's correlation coefficient = 0.56, p-value < .001; Supporting information 2), although this was found in the absence of drought stress. Kamara et al (2017) reported that increased cowpea total biomass contributed to greater seed yield, based on the positive correlations between canopy height and fodder yield with seed yield. Positive correlations between canopy height and plant biomass with canopy CO 2 assimilation were found in our study (Pearson's correlation coefficient = 0.48, pvalue < .001; Supporting information 2), which may indicate that improvement in canopy photosynthesis may contribute to increased seed yield.…”
Section: Cowpea Water-use Efficiencymentioning
confidence: 99%
“…In addition, inclusion of cowpea in the cropping system can contribute to restoration of soil fertility through the fixation of atmospheric nitrogen (Fatokun, Tarawali, Singh, Kormawa, & Tamò, 2002). Yet productivity of cowpea in Africa is low with average yields ranging 100–400 kg/ha (Kamara et al., 2017). For comparison with another dry bean, the average yield in the USA for soybean was 3,500 kg/ha in 2018 (USDA National Agricultural Statistics Service, 2019).…”
Section: Introductionmentioning
confidence: 99%